Thermodynamic model of the evaporation process of liquid residues of the propellant components in the orbital stage of the launch vehicle. (September 2018) - Trushlyakov, V.; Kudentsov, V.; Matyushin, D.; Buryak, A.
Abstract: The problem of passivation of rocket-carriers upper stages propellant tanks containing residual propellant components is under consideration. Based on the introduction of boundary conditions in the form of the heat equation with boundary conditions corresponding to the uniform distribution of the liquid residues of the rocket propellant components (RPC), a multilevel mathematical model of convective heat transfer is developed. The effect of dispersed material in the form of aluminum nanopowders on the evaporation of liquid kerosene residues is studied. The results of kerosene residues evaporation processes for a heat carrier based on combustion products of asymmetric dimethylhydrazine and nitrogen tetroxide are considered, taking into account the additives of the dispersed material. Highlights: The problem of passivation of rocket-carriers upper stages propellant tanks. Multilevel mathematical model of convective heat transfer is developed. Heat carrier based on burning of asymmetric dimethylhydrazine and nitrogen tetroxide. The effect of aluminum nanopowders on the evaporation of liquid kerosene residues.